When Does Intimate Partner Violence Continue After Separation?. (May 2013) - Ornstein, Petra; Rickne, Johanna
Over their lifetime, approximately 10% of all women become victims of postseparation stalking or assault. We use a nationally representative survey of separated Swedish women to examine whether men who strive to control their partners during their relationships are more likely to stalk or assault their ex-partners after separation. The empirical analysis shows that basic measures of control behaviors explain 18% of the variance in stalking victimization and 8% of the assault victimization. Moreover, the predictive values of our measures of control by far surpass those of other common risk markers included in the analysis.